The Influence of Green Advertising, Green Products, and Social Media on Purchasing Decision Via Brand Image - Sariah,; Halik, Abdul; Prastiwi, Estik Hari (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
Issues regarding the environment are starting to become one of the main factors of concern for society today. Likewise, the government has taken various steps to deal with environmental problems, such as making policies that state that companies must produce environmentally friendly products. The aim of this research is to determine the influence of Green Advertising, Green Products, Social Media on purchasing decisions via Brand Image among Starbucks Coffee Surabaya consumers. This research uses quantitative methods with primary data sources obtained from distributing questionnaires via Google Forms. The research population is the people of Surabaya who have purchased Starbucks products. The selection of respondents was carried out using a non-probability sampling method with a total of 100 respondents based on the Lemeshow formula calculation. The data analysis method uses descriptive analysis and SEM-PLS analysis. The research results show that the variables Green Advertising, Green Product, Social Media have a positive and significant effect on purchasing decisions via Brand Image for Starbucks Coffee Surabaya consumers.